Antibacterial and wound healing activities of elephantopus scaber plant - Muhamad Ikram Bin Jamaludin (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
In this era, researchers have discovered that the plant based drug has ability to treat many ailment and diseases. The new pharmaceuticals development from the plants based drug has gained a great attention in worldwide. These phenomena happened after people realized that wound could become the major cause of physical disabilities. The process of wound healing could be delayed if there is microbial infection. Despite to these problems, this study was specifically highlight the ability of Elephantopus scaber in enhancing the healing process of wound. The plant undergo antibacterial test by using disk diffusion method. The leaves and roots extract of this plant were tested against two types of bacteria which are Bacillus cereus and Streptococcus pyogens. The wound healing abilities of E. scaber was studied by using excision model testing on Albino mice. The presence of secondary metabolites was identified by conducting phytochemical analysis. Results show that methanolic extract of leaves part showed high area of inhibiton zone at 200 mg/ml concentration of crude extract in both bacteria B. cereus and S. pyogens which are 15 mm and 11 mm, respectively. The result of wound closure for both extracts were compared to control and found significant with the p-value was 0.0058. The analysis of phytochemical denoted that cardiac glycoside, flavonoid, steroid and terpenoid were present in both leaves and roots powder of E. scaber.